Estudio de prefactibilidad para la instalación de un criadero de trucha arco iris (Oncorhynchus mykiss) y una planta de alimento balanceado en el departamento de Ancash - Valverde Aranzabal, José (2016)
This present work gives complete details abput the installations of a trout fram in cultivation cages and a plant of balanced food. Both installations are going to be located in the department of Ancash. The aim of this proyect is to sell not only eviscerated frozen trout but also the surpluses of balanced food production for trout of the extruded type of the region.